Influence of Transformational Leadership, Motivation, and Organizational Culture on the Performance of Village Employees in Jepara District - Aditya Nova Ramadhan; Much. Imron (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study aims to examine the influence of transformational leadership, motivation and organizational culture on the performance of Village employees in Jepara District. Methodology: Theresearch design used is quantitative research. The population in this study is village employees in Jepara sub-district with a total of 82 people. The total population in this study is 82 people. The sampling technique used saturated samples, so that a sample of 82 people was obtained. The primary data needed is collected by survey by distributing a questionnaire using a google form to individuals or individuals. Results: The results of this study show that transformational leadership has a significant positive effect on the performance of village employees in Jepara District, motivation has a significant positive effect on the performance of village employees in Jepara District, organizational culture has a significant positive effect on the performance of village employees in Jepara District. Findings: This study highlights the importance of good transformational leadership, high work motivation, and maintaining an organizational culture conducive to achieving high employee performance.Novelty: This study outlines the interaction between transformational leadership, motivation, and organizational  culture in the context  of employee performance in government organizations. Originality: This study contributes to employee performance regarding the productivity of village employees in Jepara district by overcoming the gap in understanding these variables. Conclusion: Practical thinking is a recommendation for village employees in Jepara sub-district to develop strategies to improve  employee performance in accordance with the expectations and goals of the organization. The population of this study is  village employees in Jepara District. Type of Paper: Quantitative empirical research.